Revitalisasi Nilai Kearifan Lokal dalam Proyek P5 di SD/MI Kota Bengkulu: Tinjauan Literatur Berbasis Kurikulum Merdeka - Ningrum, Sania Dewi Kusuma; Putri, Indira Agleo (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to examine how local wisdom values ​​can be integrated and revitalized through the implementation of the Pancasila Student Profile Strengthening Project (P5) in Elementary Schools/Islamic Elementary Schools in Bengkulu City within the Merdeka Curriculum framework. The study was conducted using a literature study method by reviewing various current academic sources that are relevant to the theme of character education and local cultural preservation. The results of the study indicate that the P5 Project provides ample space for the application of local wisdom values ​​such as mutual cooperation, tolerance, and love for the environment through a project-based learning approach. In addition, the involvement of local communities and the adaptation of teaching materials to the cultural context are important factors in the success of implementation. This study highlights the importance of revitalizing local wisdom values ​​in a structured manner through the P5 program in the context of the Merdeka Curriculum. This study provides a theoretical contribution as a reference for educators and policy makers in developing contextual and sustainable local culture-based character education strategies in the Merdeka Curriculum era.